In House Training Game Edukatif Berbasis Android Bagi Calon Guru SD Se-NTB - Nurwahidah, Nurwahidah; Suranti, Ni Made Yeni; Ibrahim, Ibrahim; Alimuddin, Nurkhaerat (Indonesian Publication Center, 2024)
Community service activities entitled